Analisa Derajat Kejenuhan, Perlengkapan Jalan, dan Nilai Kerataan Pada Jalan Raya Kepandean, Kabupaten Tegal - Hadi, Suprapto; Fatah, Muhammad Ibnu; Hutasoit, Rutjka Benela; Fahmi, Silvia Afida; Rivaldy, Muhamad Rafli (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Road safety audits are an effort to improve safety and prevent traffic accidents. The implementation of the audit can be carried out by the survey method directly in the field and can use the Hawkeye car to get the International Roughness Index (IRI) value. The results of this study show that the condition of the road on the Kepandean Highway section with the IRI value of the route from the direction of SMPN 1 Dukuhturi is 6.5 while the IRI value of the route to SMPN 1 Dukuhturi is 6.3 so that it can be concluded that the road is in the medium category (not good) and requires periodic repair and maintenance efforts